O PAPEL DA CICLOOXIGENASE-2 E DA PRESSÃO ARTERIAL NA LESÃO RENAL DE RATOS SUBMETIDOS À INFUSÃO CONTÍNUA DE ANGIOTENSINA II - Flávia Santin; Maria do Carmo Fernandez Vailati; Marcela Marcondes Pinto Rodrigues; David Michelucccci; Luis Cuadrado Martin; Denise Saretta Schwartz (Ciência Animal Brasileira, 2010)
Angiotensin II (ANGII) is a vasoconstrictor which action on inflammation has been studied. The objective of this study was to verify the stimulation of cyclooxigenase-2 and blood pressure on renal damage by ANGII. Wistar rats were distributed into four groups, as follows: group 1 – control; group 2 – ANGII; group 3 – ANGII + celecoxib; and group 4 – celecoxib. The ANGII was infused in the animals by subcutaneous osmotic mini-pumps during 72 hours. After that, euthanasia was performed. The blood pressure was measured before the drugs administration and before the euthanasia. Histopathological and immunohistochemical evaluations were performed in kidneys to assess the expression of COX-2. It was concluded that ANGII caused renal damage, regardless of blood pressure values. ANGII associated with celeboxib increased blood pressure. Celecoxib did not protect the kidneys against ANGII activities.